2020
DOI: 10.1001/jamapediatrics.2019.5316
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Psychological Distress With In Utero Brain Development in Fetuses With Congenital Heart Disease

Abstract: IMPORTANCE Prenatal maternal psychological distress can result in detrimental mother and child outcomes. Maternal stress increases with receipt of a prenatal diagnosis of fetal congenital heart disease (CHD); however, the association between maternal stress and the developing brain in fetuses with CHD is unknown.OBJECTIVE To determine the association of maternal psychological distress with brain development in fetuses with CHD. DESIGN, SETTING, AND PARTICIPANTS This longitudinal, prospective, case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 63 publications
2
60
1
1
Order By: Relevance
“…Pregnant mothers of fetuses with CHD have been found to experience high incidences of stress, depression, and anxiety. This psychological distress was associated with reduced cerebellar and hippocampal growth during the latter half of gestation when compared to healthy pregnancies (105).…”
Section: Maternal Stressmentioning
confidence: 94%
“…Pregnant mothers of fetuses with CHD have been found to experience high incidences of stress, depression, and anxiety. This psychological distress was associated with reduced cerebellar and hippocampal growth during the latter half of gestation when compared to healthy pregnancies (105).…”
Section: Maternal Stressmentioning
confidence: 94%
“…Elevated maternal psychological distress has been reported for severe and complex anomalies such as various congenital heart diseases, but also for abnormalities that are less severe and can be treated, such as cleft lip/palate. For example, in a recent study of 48 mothers carrying a fetus with complex congenital heart disease, maternal psychological distress was evident for 65% of the mothers, in contrast to 25% of those carrying a healthy fetus (Wu et al, 2020). Similarly, Rey- Bellet and Hohlfeld (2004) interviewed 29 expectant parents and found that most reacted with severe psychological shock in response to cleft lip/palate detection, but awareness that the deformity could be treated has been reported as a great relief (Nusbaum et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of prenatal diagnoses of CHD has led to a greater understanding of the vulnerability of this unique patient group, starting in utero. Elevated psychobiological markers of maternal stress during pregnancy, especially early in gestation, may correlate with altered placental function, delayed fetal maturation, and decreased cerebellar and hippocampal volumes in fetuses with CHD [ 26 ]. In addition, these markers may be associated with disrupted emotional regulation and impaired cognitive performance during infancy, and decreased brain volume in areas associated with learning and memory in 6- to 8-year-old children [ 27 ].…”
Section: Discussionmentioning
confidence: 99%